Requirement of a leucine residue for (apical) membrane expression of type IIb NaPi cotransporters - Karim-Jimenez, Zoubida (The National Academy of Sciences, 2000)
Type II NaPi cotransporters mediate epithelial phosphate (P(i)) reabsorption. In mammals the type IIb protein is expressed in the small intestinal apical membrane and other epithelia; it is not expressed in the renal proximal tubule where we find the type IIa isoform. To look for molecular determinant(s) involved in apical expression of type IIb cotransporters, we have made deletion mutations within the C-terminal tails of mouse IIb (mIIb) and human IIb (hIIb) transporter proteins. The constructs were fused to the enhanced green fluorescent protein and transiently transfected into intestinal CaCo2-cells. Both mIIb and hIIb were located exclusively in the apical membrane of the cells. For mIIb, the removal of a cysteine cluster or the last three amino acids (TVF) had no effect on the location of the protein. However, truncation at the level of the conserved L691/689 prevented the apical membrane expression of both mIIb and hIIb, respectively, and the mutated proteins were located in endosomal and lysosomal structures. A similar expression pattern of the mIIb and hIIb constructs was found in renal proximal tubular opossum kidney cells. Our data suggest that L691/689 is involved in mechanisms leading to an apical expression of type IIb NaPi cotransporters.